Midwives' knowledge, attitudes and confidence in discussing maternal and childhood immunisation with parents: A national study. Issue 2 (10th January 2020) - Frawley, Jane E.; McKenzie, Kirsty; Sinclair, Lynn; Cummins, Allison; Wardle, Jon; Hall, Helen
Abstract: Introduction: Despite the enormous benefits of childhood and maternal immunisation to individual and population health, the uptake of maternal vaccines during pregnancy remains suboptimal. Midwives are a trusted information source for parents and play an important role in the provision of immunisation information. Understanding midwives' attitudes and vaccine knowledge, along with their confidence to discuss maternal and childhood immunisation with parents, is key to reducing parental decisional conflict and achieving immunisation goals. Methods: An online study was conducted to investigate midwives' knowledge and attitudes towards maternal and childhood vaccination along with their confidence to answer parents' vaccine-related questions. Midwives were recruited by email via the midwifery peek body, the Australian College of Midwives. Results: A total of 359 midwives completed the online survey. The majority of midwives supported maternal (influenza 83%, pertussis 90.5%) and childhood immunisation (85.8%); however, 69.4% of respondents wanted further training about immunisation. Midwives who felt their midwifery education adequately covered immunisation were more confident advising parents about maternal ( p  = 0.007) and childhood immunisation ( p  < 0.001). Similarly, Midwives were significantly more likely to confidently advise parents about maternal ( p  < 0.001) and childhood immunisations ( p  < 0.001) if they had completed a specific immunisation training course outside of their midwifery course. Conclusion: Most midwives working in Australia support vaccination. However, access to contemporary, culturally appropriate education that enables midwives to engage confidently with parents about immunisation is lacking. Education based on a women-centred approach within the pre-registration curriculum along with continuing professional development programs could enable midwives to reduce the evidence to practice gap by increasing vaccine uptake.